Summer Thermal Comfort in Russian Big Cities (1966-2015) - Konstantinov, Pavel; Tattimbetova, Diana; Varentsov, Mikhail; Shartova, Natalia (Geographica Pannonica, 2021)
The main goal of the study is the assessment of modern bioclimatic conditions (1966-2015) for determining the level of comfort in large Russian cities based on the observations at the meteorological stations, including Physiological Equivalent Temperature (PET) for the main extent of thermal comfort. According to the distribution of thermal stress events (calculated for meteorological fix hours, 8 times per day) the authors created the comfort diagram for each city during daytime heat wave period and evaluated their comfort conditions. In the current research we are operating with WMO climatic data for eleven biggest cities of the Russian Federation: from the European part (Moscow, Saint-Petersburg, Ekaterinburg, Voronezh, Volgograd, Kazan, Nizhny Novgorod, Perm, Ufa) and from Siberia (Omsk and Krasnoyarsk). The most interesting result of the comparison of the long-period (50 years) urban trends (PET-index and Air Temperature) in different parts of Russia is its extraordinary cross-shaped form in Moscow (in other cities the trends lines are practically parallel to each other). It means that at the level of the average annual values, only in Moscow the PET index (and, hence, potentially the thermal stress) grows faster than the regional climate warms. In other cities this tendency is much weaker (N.Novgorod) or not significant. This interesting tendency is caused by both Moscow related urban planning dynamics in post-USSR period and by regional climate dynamics.
Keywords: Physiological Equivalent Temperature (PET); regional urban climate; urban thermal comfort, Russian Federation, climate trends